Determinants of sustainable development dimension among leaders of rural community: a case study of Malaysia - Abu Samah, Bahaman; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Academic Journals, 2009)
Rural development researchers have identified a number of factors that affect sustainable development among the rural community. Nevertheless, mix results were reported in literature. Hence, this study was conducted to investigate on the constructs that affect sustainable development among members of Village Development and Security Committee (VDSC) under the Vision Village Movement (VVM). A total of 235 respondents from 18 villages were involved encompassing three states in Malaysia. The final model derived from this study showed that four pertinent constructs that fit into the sustainable development model are spirituality, leadership, beautification, and education. It is believed that the findings of this study would add new perspective in understanding the complexities associated with sustainable development among the rural community.